PENGARUH PENERAPAN MODEL MODEL LEARNING CYCLE 5E PADA MATERI INVERTEBRATA TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR KOGNITIF SISWA KELAS X SMA MUHAMMADIYAH 7 SURABAYA - Anggi Budi Abriliyani; Yuni Gayatri; Wiwi Wikanta (Pedago Biologi : Jurnal Pendidikan dan Pembelajaran Biologi, 2017)
Abstrak: This study aims to (1). determine the effect of learning model Learning Cycle 5E on the material Invertebrates of the science process skills of students (2) the effect of the model Learning Cycle 5E on the material invertebrates effect on cognitive learning outcomes of students (3) determine the ability of teachers to manage learning biology through learning model Learning Cycle 5E in improving skills and the cognitive learning process of students. This study is a quasi experimental research with the study design using the design of "The Non-Equivalent Control Group". The sample in this research is class X SMA Muhammadiyah 7 Surabaya. Data collected with the test and non-test (observation) using research instruments observation sheet teachers 'skills in the management of learning, observation sheet skill students' science process, pretest and posttest. Data were analyzed descriptively and quantitatively test statistic T. From these results it can be concluded that: (1) There is an effect Learning Cycle 5E learning model on Invertebrate material to the students' science process skills; (2) Model Learning Cycle 5E on Invertebrate material effect on cognitive learning outcomes of students. The average value of completeness in classical the experimental class amounted to 78.2%; (3) ability to understand biology teachers manage learning by using Learning Cycle 5E models in enhancing science process skills of students and student learning outcomes SMA Muhammadiyah 7 Surabaya in he very good category.